CFD modeling of mixing/segregation behavior of biomass and biochar particles in a bubbling fluidized bed - Sharma, Abhishek; Wang, Shaobin; Pareek, Vishnu; Yang, H.; Zhang, D. (Pergamon, 2014)
Computational Fluid Dynamics (CFD) simulations have been carried out to examine the hydrodynamics of a mixture of biomass and biochar particles in a bubbling fluidized bed. The effect of superficial gas velocity, biomass density and particle size on the mixing/segregation behavior of biomass–biochar mixture was analyzed using the Euler–Euler (EE) model. It was observed that on increasing the superficial gas velocity, the bubbles size increased which led to better mixing of both biomass and biochar particles. The biomass density had a significant impact, but particle size had a little impact on the distribution of biomass particles in the biochar bed. Simulations were conducted in both 2-dimensional (2-D) and 3-dimensional (3-D) configurations, and were validated using the available experimental data. A sensitivity analysis was also carried out for examining the effect of different gas–solid drag correlations, wall boundary conditions and particle–particle restitution coefficient. For the operating conditions considered in this study, it was determined that the choice of drag coefficient correlation, particle–wall and particle–particle interaction parameters had a considerable impact on the hydrodynamics of the biomass–biochar mixture.